Identifying novel heterozygous PI4KA variants in fetal abnormalities - Chen Cheng; Fan Yang; Xinlin Chen; Sheng Zhao (BMC Medical Genomics)
Abstract Background The clinical manifestations of PI4KA-related disorders are characterized by considerable variability, predominantly featuring neurological impairments, gastrointestinal symptoms, and a combined immunodeficiency. The aim of this study was to delineate the novel spectrum of PI4KA variants detected prenatally and to assess their influence on fetal development. Methods A thorough fetal ultrasound screening was conducted, supplemented by both antenatal and post-abortion magnetic resonance imaging (MRI) studies. Novel PI4KA variants were detected through clinical Whole exon sequencing (WES) and validated by Sanger sequencing. The functional consequences of these variants were evaluated using bioinformatics tools. The effects of the identified variants on splicing were analyzed through minigene splicing assays. Subsequently, both wild-type and mutant PI4KA protein fragments were purified, and their enzymatic activities were quantitatively assessed. Results Ultrasound imaging, MRI scans revealed a dilated small intestine with an obstruction. Compound heterozygous variants (NM_058004.3: c.2802_2863-40del and c.2819 C > T, p.Ala940Val) were identified in the PI4KA of the affected fetus through clinical trio-WES. Both variants were predicted deleterious. The PI4KA variant c.2802_2863-40del resulted in the production of three distinct mRNA isoforms. The PI4KA variant c.2819 C > T (p.Ala940Val) significantly reduced the enzyme activity. Conclusions This study extended the mutational spectrum of PI4KA and may provide guidance for genetic counseling. Functional studies confirmed that the identified variant induces alterations in RNA splicing and impairs enzyme activity.